Using Simulation to Teach Methods for Improving Patient Literacy about Medicines - Vivienne Mak; Anisha Kaur Sandhu; Sunanthiny Krishnan (MDPI AG, 2020)
Pharmacists have a role in educating patients on the self-management of their medications, using accurate medicines lists. Thus, pharmacy students need to be adequately trained and assessed in health-literacy skills to be competent for future patient-education consultations using medicines lists. Performance-based assessments using patient simulation are often utilized to examine students' competence in clinical knowledge and communication skills. Due to COVID-19, education systems changed to remote online delivery utilizing video conferencing platforms (i.e., ZoomTM), which proved challenging for performance-based assessments. These challenges include difficulty in observing non-verbal cues over ZoomTM and not having adequate internet access. Adaptations to reduce reliance on internet access were made where students submitted a video-recording task wherein they educated a simulated patient on a medicines list, under lockdown restrictions during the pandemic. A total of 304 submissions were received where students performed the role-play with a simulated patient, such as their family members, housemates or peers either at home in person or via ZoomTM. Although it was not an original goal of the task, the collaborative effort between pharmacy instructors, students and the public helped increase awareness of medicines lists through this task.